Family physicians’ attitudes and practice on screening and prevention of fragility fractures, and shared decision-making with postmenopausal women: a qualitative study in Spain - Montserrat León-García; Esther Cánovas Martínez; Yolanda Álvarez Pérez; María Antonia Pou; Alberto López García-Franco; Ana Sanz Bas; Sara Rodriguez-Moreno; Claudia Erika Delgado Espinoza; Pablo Roca; Aránzazu González Osuna; Diana Fernández Valverde; Betzabeth Marín Nanco; et al. (BMC Primary Care)
Abstract Background Osteoporosis is a prevalent condition among postmenopausal women, significantly increasing the risk of fragility fractures. Despite the availability of clinical guidelines, their implementation in primary care, remains highly variable, particularly regarding fracture prevention and shared decision-making (SDM). Methods We conducted a qualitative study to explore the attitudes and practices of Spanish family physicians in preventing fractures among postmenopausal women. Sixteen semi-structured interviews were conducted with physicians from diverse socioeconomic backgrounds and levels of clinical experience. Data were analysed using an iterative, theory-driven approach to identify key themes and barriers. Results Physicians showed substantial variability in fracture risk assessment approaches, frequently combining tools such as FRAX with clinical judgment. Most were cautious about prescribing bisphosphonates for primary prevention, citing concerns about the strength of the evidence and potential adverse effects. While non-pharmacological strategies, such as lifestyle modifications and fall prevention, were emphasized, their implementation was often constrained by workload pressures. Patient involvement in decision-making was hindered by widespread misconceptions about osteoporosis and its treatment, as well as the lack of appropriate decision-support tools. Participants highlighted the need for clearer guidelines, enhanced educational resources, and accessible decision aids to facilitate patient engagement in care. Conclusions This study highlights the complex challenges family physicians face in fracture prevention among postmenopausal women, including heterogeneity of recommendations in guidelines, limited SDM implementation, and systemic barriers within primary care. Addressing these issues will require multifaceted interventions targeting both healthcare system constraints and patient education. Future efforts should focus on developing and implementing strategies that support evidence-based, patient-centred decision-making while accounting for the realities of primary care practice.